Influence of ro-vibrational and isotope effects on the dynamics of the C(3P)+ OD(X2) CO(X1 ?+) + D(2S) reaction - Jorfi, Mohamed; Honvault, Pascal; Bussery-Honvault, Beatrice; Banares, Luis; Bulut, Niyazi (Taylor & Francis Ltd, 2011)
The C(3P)+OD(X2) reaction has been studied by means of quantum mechanical real wave packet (RWP) and quasiclassical trajectory (QCT) methodologies on the ground potential energy surface of Zanchet et al. [J. Phys. Chem. A 110, 12017 (2006)]. Initial state selected total reaction probabilities at J = 0 total angular momentum have been calculated for a wide range of collision energies. Product state-resolved integral cross-sections at selected collision energies and excitation functions have been determined from the RWP calculations using the J-shifting approximation and from QCT calculations. State-specific and thermal rate coefficients have been calculated using both methodologies up to 500 K. The effect of reagent rotational excitation on the dynamics for the C(3P)+OH(X2) and C(3P)+OD(X2) reactions has been investigated and interesting discrepancies between the QCT and RWP results have been found. The RWP results are found to be in an overall good agreement with the corresponding QCT results, although the QCT integral cross-section and rate coefficients are slightly smaller than those obtained from the RWP calculations.
Keywords: reaction dynamics; gas phase reactions; quantum dynamics; reactive collisions